The Babylonian astronomical compendium MUL.APIN - Hunger, Hermann 1942-; Steele, John M. (Routledge, 2019)
"MUL. APIN, written sometime before the 8th century BC, was the most widely copied astronomical text in ancient Mesopotamia: a compendium including information such as star lists, descriptions of planetary phases, mathematical schemes for the length of day and night, a discussion of the luni-solar calendar and rules for intercalation, and a short collection of celestial omens. This book contains an introductory essay, followed by a new edition of the text and a facing-page transliteration and English translation. Finally, the book contains a new and detailed commentary on the text. This is a fascinating study, and an important resource for anyone interested in the history of astronomy."--
Keywords: Astronomy, Assyro-Babylonian; Astronomy, Ancient; Stars / Catalogs